Criterion Validity of Cognitive Reflection for Predicting Job Performance and Training Proficiency: A Meta-Analysis - Otero, Inmaculada; Salgado, Jesús F.; Moscoso, Silvia (Frontiers in Psychology, 2021)
This article presents a meta-analysis of the validity of cognitive reflection (CR) for predicting job performance and training proficiency. It also examines the incremental validity of CR over cognitive intelligence (CI) for predicting these two occupational criteria. CR proved to be an excellent predictor of job performance and training proficiency, and the magnitude of the true validity was very similar across the two criteria. Results also showed that the type of CR is not a moderator of CR validity. We also found that CR showed incremental variance over CI for the explanation of job performance, although the magnitude of the contribution is small. However, CR shows practically no incremental validity over CI validity in the explanation of training proficiency. Finally, we discuss the implications of these findings for the research and practice of personnel selection.